Anterior Auditory Field Is Needed for Sound Categorization in Fear Conditioning Task of Adult Rat - Shi, Zhiyue; Yan, Sumei; Ding, Yu; Zhou, Chang; Qian, Shaowen; Wang, Zhaoqun; Gong, Chen; Zhang, Meng; Zhang, Yanjie; Zhao, Yandong; Wen, Huizhong; Chen, Penghui; et al. (Frontiers in Neuroscience, 2019)
Both primary auditory cortex (A1) and anterior auditory field (AAF) are core regions of auditory cortex of many mammalians. While the function of A1 has been well documented, the role of AAF in sound related behavioral remain largely unclear. Here in adult rats, sound evoked fear conditioning paradigm, surgical ablation and chemogenetic manipulations were used to examine the role of AAF in fear related sound context recognition. Precise surgical ablation of AAF cannot block sound evoked freezing behavior but the fear conditioning became non-selective to acoustic cue. Reversible inhibition of AAF using chemogenetic activation at either training or testing phase can both lead to strong yet non-selective sound evoked freezing behavior. These simple yet clear results suggested that in sound evoked fear conditioning, sound cue and detailed content in the cue (e.g. frequency) are processed through distinct neural circuits and AAF is a critical part in the cortex dependent pathway. In addition, AAF is needed and playing a gating role for precise recognition of sound content in fear conditioning task through inhibiting fear to harmless cues.